2009
DOI: 10.1007/s10021-009-9275-z
|View full text |Cite
|
Sign up to set email alerts
|

Exotic Ecosystem Engineers Change the Emergence of Plants from the Seed Bank of a Deciduous Forest

Abstract: The anthropogenic spread of exotic ecosystem engineers profoundly impacts native ecosystems. Exotic earthworms were shown to alter plant community composition of the understory of deciduous forests previously devoid of earthworms. We investigated the effect of two exotic earthworm species (Lumbricus terrestris L. and Octolasion tyrtaeum Savigny) belonging to different ecological groups (anecic and endogeic) on the emergence of plants from the seed bank of a northern North American deciduous forest using the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 42 publications
2
45
1
Order By: Relevance
“…Earthworms may be important seed and seedling predators with potentially strong effects on plant community composition [41]. Although interactions between earthworms and tree seeds have, to our knowledge, not been investigated, studies on herbaceous species stress strong selective pressure by earthworms on the fate of seeds, which is likely to change plant community composition of North American forest ecosystems [42]. Plant species not adapted to the presence of earthworms may suffer from their invasion, resulting in simplified herbaceous communities [39], which also play an important role in forest ecosystem function [43].…”
Section: Interactions Of Herbivores Detritivores and The Plant Commumentioning
confidence: 99%
“…Earthworms may be important seed and seedling predators with potentially strong effects on plant community composition [41]. Although interactions between earthworms and tree seeds have, to our knowledge, not been investigated, studies on herbaceous species stress strong selective pressure by earthworms on the fate of seeds, which is likely to change plant community composition of North American forest ecosystems [42]. Plant species not adapted to the presence of earthworms may suffer from their invasion, resulting in simplified herbaceous communities [39], which also play an important role in forest ecosystem function [43].…”
Section: Interactions Of Herbivores Detritivores and The Plant Commumentioning
confidence: 99%
“…In Minnesota, Larson et al (2010) found that sugar maple trees growing in invaded conditions were more sensitive to drought than trees growing in earthworm-free conditions. Other studies suggest that worm selectivity in seedling ingestion and their alteration of seedbed conditions can profoundly change plant community composition in deciduous forests (Hale et al 2005Frelich et al 2006;Holdsworth et al 2007;Eisenhauer et al 2009). The effects of liming on earthworms will be discussed further in section 4.3.…”
Section: Forest Stand and Catchmentmentioning
confidence: 99%
“…One of the most documented ecosystem alterations by non-native earthworms is the modification of the northern American hardwood forests following the colonization by European earthworms (Frelich et al, 2006;Hale et al, 2005). Indirect impacts of earthworms on plant community via soil modifications have also often been reported (Eisenhauer et al, 2009b(Eisenhauer et al, , 2007Holdsworth et al, 2007;Nuzzo et al, 2009), but only two studies have focused on the direct impact of non-native, invasive earthworms on plant communities through seed ingestion (Drouin et al, 2014;Eisenhauer et al, 2009b). In the first study, the effects of invasive earthworms, Lumbricus terrestris and Octoaedra tyrtaeum on seedling emergence in American northern hardwood forests were examined (Eisenhauer et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Indirect impacts of earthworms on plant community via soil modifications have also often been reported (Eisenhauer et al, 2009b(Eisenhauer et al, , 2007Holdsworth et al, 2007;Nuzzo et al, 2009), but only two studies have focused on the direct impact of non-native, invasive earthworms on plant communities through seed ingestion (Drouin et al, 2014;Eisenhauer et al, 2009b). In the first study, the effects of invasive earthworms, Lumbricus terrestris and Octoaedra tyrtaeum on seedling emergence in American northern hardwood forests were examined (Eisenhauer et al, 2009b). The presence of the endogeic O. tyrtaeum significantly increased the emergence of all seedlings while the presence of the anecic L. terrestris increased the emergence of herb seedlings only.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation